Changes of COVID-19 Knowledge, Attitudes, Practices and Vaccination Willingness Among Residents in Jinan, China - Jiang, Ning; Yang, Cheng; Yu, Wenjing; Luo, Liyan; Tan, Xin; Yang, Liping (Frontiers in Public Health, 2022)
Background: Vaccine hesitancy is responsible for lower low vaccine coverage and increased risk of epidemics. The purpose of this study was to assess whether public knowledge, attitudes, practices, and willingness to vaccinate against COVID-19 have changed over time and at different stages of vaccination. Methods: Two consecutive surveys were conducted among residents of the Leshan community in Jinan from May to June,2021 (n = 423) (basic dose vaccination phase) and from December, 2021 to January, 2022(n = 470) (booster vaccination phase). Randomly sampling was used in residents to complete an anonymous questionnaire. Chi-square test was used to compare the changes in knowledge, attitudes and practices of the subjects in different survey stages. Multivariable logistic regression analysis was used to explore factors related to vaccination hesitancy. Results: In the booster vaccination phase, protective behaviors (89.9% vs. 74.5%) of residents increased significantly compared with the basic vaccination phase. Residents are more hesitant to receive booster doses than basal doses of COVID-19 vaccine (OR: 18.334, 95% CI: 9.021–37.262). Residents with other marital statuses (OR: 2.719, 95% CI: 1.632-4.528), negative attitudes towards government measures are more hesitant to get vaccinated (OR: 2.576, 95% CI: 1.612–4.118). People who thought their physical condition was very good or good were more likely to be vaccinated than those who thought they were in fair or poor health (OR: 0.516, 95% CI: 0.288-0.925; OR: 0.513, 95% CI: 0.295-0.893). Young people inclined to use new media (such as WeChat and microblog) to obtain information, while the elderly to use traditional methods (such as television). Government propaganda, residents' perception of the importance of vaccines and the risk of disease were the main reasons for accelerating residents to vaccinate. The main reasons affecting residents’ lack of vaccination were contraindications to the vaccine or inconvenient time for vaccination. Conclusions: Vaccine hesitancy increased significantly with change in vaccination stage. Strategies should be adopted to increase vaccination coverage such as improving the convenience of vaccination, promoting through multiple channels.